2018
DOI: 10.3390/bs8010013
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated Fowl: The Complex Behaviour and Cognitive Skills of Chickens and Red Junglefowl

Abstract: The world’s most numerous bird, the domestic chicken, and their wild ancestor, the red junglefowl, have long been used as model species for animal behaviour research. Recently, this research has advanced our understanding of the social behaviour, personality, and cognition of fowl, and demonstrated their sophisticated behaviour and cognitive skills. Here, we overview some of this research, starting with describing research investigating the well-developed senses of fowl, before presenting how socially and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 144 publications
(237 reference statements)
0
30
0
Order By: Relevance
“…Personality traits, in general, have been shown to influence learning in wild as well as in domesticated animals ( Lansade and Simon, 2010 ; Guenther et al, 2014 ; de Haas et al, 2017a , b ; Zidar et al, 2017 ). Furthermore, those traits have been described in fowl ( Favati et al, 2015 ; Zidar et al, 2017 ; Dudde et al, 2018 ) and traits like sociality or fearfulness show some degree of heritability ( Jensen, 2006 ; Garnham and Løvlie, 2018 ). Fearful hens, for example, may be poorer learners than less-fearful conspecifics ( de Haas et al, 2017a , b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality traits, in general, have been shown to influence learning in wild as well as in domesticated animals ( Lansade and Simon, 2010 ; Guenther et al, 2014 ; de Haas et al, 2017a , b ; Zidar et al, 2017 ). Furthermore, those traits have been described in fowl ( Favati et al, 2015 ; Zidar et al, 2017 ; Dudde et al, 2018 ) and traits like sociality or fearfulness show some degree of heritability ( Jensen, 2006 ; Garnham and Løvlie, 2018 ). Fearful hens, for example, may be poorer learners than less-fearful conspecifics ( de Haas et al, 2017a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Chickens are known to possess a complex behavioral repertoire, including sophisticated cognitive abilities ( Krause et al, 2006 ; Nicol, 2015 ; Marino, 2017 ; Garnham and Løvlie, 2018 ). Like other animals, they use learning as a key mechanism to adapt to their physical and social environment ( Jensen, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate how behaving in a more proactive manner, as well as aspects of cognition and affective state may influence the initiation and outcome of contests, we exposed sexually mature male and female red junglefowl (Gallus gallus) to a battery of behavioral assays (novel object-, novel arena-, tonic immobility-, and restrained intruder test) and cognitive tests (discriminative learning-, detour reaching-, and cognitive judgement bias tests) before staging intra-sexual contests between morphologically matched individuals. Red junglefowl live naturally in social groups of 2-15 individuals (reviewed in Garnham and Løvlie 2018), in which males and females form separate social hierarchies through intra-sexual contests (Banks 1956;Guhl 1968). Initiators of contests often win them (Ligon et al 1990;Favati et al 2014a), which result in higher social positions and increased access to resources (e.g., food, mating partners, Collias et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. It appears that birds' environmental needs may vary not only between species but also between breeds [3] and individuals of the same breed [4]. Previous investigations [3,5] have demonstrated that hens from three different breeds (green-legged partridge-Zk, Polbar-Pb, and Leghorn-Lg) kept in environments as identical as possible not only differed in the level of activity, emotional arousal, or degree of curiosity, but also preferred different enrichments of the environment, which collectively resulted in a different level of stress in the birds [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since the behavioural patterns depend on the genetic background, previous bird's experiences, environmental conditions prevailing during embryonic development, and epigenetic effects [4,[6][7][8][9], a question was posed whether the differences observed in the behaviour of the three breeds (Zk, Lg, Pb) were innate breed-specific behavioural patterns or whether they were "generated" by their living environment. In other words, the question was whether the rearing practice, which was not adjusted to the genetic predisposition of the breed, was the cause of the behavioural differences or whether the breed-specific differences occurred regardless of the rearing practices.…”
Section: Introductionmentioning
confidence: 99%